CYP1A2 genetic polymorphisms are associated with treatment response to the antidepressant paroxetine. (November 2010) - Lin, Keh-Ming; Tsou, Hsiao-Hui; Tsai, I-Ju; Hsiao, Mei-Chun; Hsiao, Chin-Fu; Liu, Chia-Yih; Shen, Winston W; Tang, Hwa-Sheng; Fang, Chun-Kai; Wu, Chi-Shin; Lu, Shao-Chun; Kuo, Hsiang-Wei; et al.
Aim: Paroxetine is a drug of choice in the treatment of major depressive disorder (MDD). Its metabolism has recently been reported to be mediated through the CYP enzymes 1A2 and 2D6. In our current study, we tested whether genetic polymorphisms in CYP1A2 are associated with the treatment efficacy and side effects of paroxetine.Materials & methods: A total of 241 MDD patients who had taken paroxetine continually for 8 weeks were recruited, and their steady state paroxetine concentrations were measured at weeks 2, 4 and 8. The genotypes of these patients were then assessed for the presence of nine SNPs, which were selected from either the HapMap Chinese ethnic group, the literature report or through their functional role in the CYP1A2 gene.Results: The allele types for SNPs rs4646425 (permutation p = 0.03), rs2472304 (permutation p = 0.01) and rs2470890 (permutation p = 0.004) demonstrated significant associations with paroxetine treatment remission at week 8. Response rates in the Hamilton Rating Scale for Depression (HAM-D) and for The Hamilton Rating Scale for Anxiety (HAM-A) were significantly associated with the SNPs rs4646425 (p = 0.0126 and 0.0088 for HAM-D and HAM-A, respectively) and rs4646427 (p = 0.0067 and 0.0196 for HAM-D and HAM-A, respectively). The inducible SNP rs762551 had a significant association with paroxetine dose at week 4 (permutation p = 0.012). We did not find an association between these SNPs and the side effects or serum concentrations of paroxetine. Conclusion: Genetic variants in the CYP1A2 region may be indicators of treatment response in MDD patients to paroxetine.